Handbook of Optimization in Complex Networks Communication and Social Networks - Thai, My T.; Pardalos, Panos M.; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
This second volume of the "Handbook Optimization in Complex Networks" presents the most recent research and developments in the application of optimization techniques to the study of complex communication and social networks. This book present several optimization models and their application to a variety of network settings including: online social networks, wireless communication networks, as well as models that describe virus and social media propagation. This book can serve as a useful resource to any student or researcher interested in the application of optimization techniques to communication and or social networks.
Preface -- 1. Structural Vulnerability and Robustness in Complex Networks: Different Approaches and Relationships between Them (R. Criado, M. Romance) -- 2. Optimizing Network Topology for Cascade Resilience (A. Gutfraind) -- 3. Optimizing Synchronization, Flow, and Robustness in Weighted Complex Networks (G. Korniss, R. Huang, S. Sreenivasan, B.K. Szymanski) -- 4. Joint Optimization of Resources and Routes for Minimum Resistance: From Communication Networks to Power Grids (A. Tizghadam, A. Bigdeli, A. Leon-Garcia, H. Naser) -- 5. Clique Relaxation Models in Social Network Analysis (J. Pattillo, N. Yourssef, S. Butenko) -- 6. Application Traffic Activity Graph Analysis (Y. Jin, E. Sharafuddin, Z.-L. Zhang) -- 7. Localized Bridging Centrality (S. Nanda, D. Kotz) -- 8. On Throughput Maximization Problem for UWB-Based Sensor Networks via Reformulation-Linearization Technique (Y. Shi, Y.T. Hou, H.D. Sherali) -- 9. A Parallel Routing Algorithm for Traffic Optimization (M.L. Wang, K.H. Yeung, and F. Yan) -- 10: Internet based Service Networks (L.-Y. Cui, S. Kumara, R. Albert) -- 11. On Detection of Community Structure in Dynamic Social Networks (N. P. Nguyen, Y. Xuan, M. T. Thai) -- 12: Path Formation in Human Contact Networks (N. Sastry, P. Hui) -- 13. Social Forwarding in Mobile Opportunistic Networks: A case of PeopleRank (A. Mtibaa, M. May, M. Ammar) -- 14. Discount Targeting in Online Social Networks Using Backpressure-Based Learning (S. Shakkottai, L. Ying) -- 15. Social-Aware Data Diffusion in Delay Tolerant MANETs (Y. Zhang, W. Gao, G. Cao, T. La Porta, B. Krishnamachari, A. Iyengar) -- 16. Security and Privacy in Online Social Networks: Optimization Perspectives (L. Ding, H. Du, W. Wu) -- 17. A Social Network Based Patching Scheme for Worm Containment in Cellular Networks (Z. Zhu, G. Cao, S. Zhu, S. Ranjan, A. Nucci).
Keywords: Mathematics; Computer Communication Networks; Mathematical optimization; Telecommunication; Mathematics; Optimization; Computer Communication Networks; Communications Engineering, Networks